School performance and genetic propensities for educational attainment and depression in the etiology of self-harm: a Danish population-based study. (1st February 2023) - Sørensen, Holger J.; Antonsen, Sussie; Benros, Michael E.; Erlangsen, Annette; Albiñana, Clara; Nordentoft, Merete; Børglum, Anders D.; Mors, Ole; Werge, Thomas; Mortensen, Preben B.; Hougaard, David; Webb, Roger T.; et al.
Abstract: Background: Poor school performance is linked to higher risks of self-harm. The association might be explained through genetic liabilities for depression or educational attainment. We investigated the association between school performance and self-harm in a population-based sample while assessing the potential influence of polygenic risk scores (PRSs) for depression (PRSMDD ) and for educational attainment (PRSEDU ). Method: We conducted a follow-up study of individuals born 1987–98 and followed from age 18 until 2016. The total sample consisted of a case group (23, 779 diagnosed with mental disorders; schizophrenia, bipolar disorder, depression, autism, and attention deficit hyperactivity disorder (ADHD) and a randomly sampled comparison group ( n  = 10, 925). Genome-wide data were obtained from the Neonatal Screening Biobank and information on school performance, family psychiatric history, and socioeconomic status from national administrative registers. Results: Individuals in the top PRSMDD decile were at higher self-harm risk in the case group (IRR: 1.30; 95% CI 1.15–1.46), whereas individuals in the top PRSEDU decile were at lower self-harm risk (IRR: 0.63; 95% CI: 0.55–0.74). Poorer school performance was associated with higher self-harm risk in persons diagnosed with any mental disorder (IRR: 1.69; 95% CI: 1.44–1.99) and among the comparison group (IRR: 7.93; 95% CI: 4.47–15.18). Observed effects of PRSMDD and PRSEDU on self-harm risk were strongest for individuals with poor school performance. Conclusion: Associations between PRSMDD and self-harm risk and between PRSEDU and self-harm risk were found. Nevertheless, these polygenic scores seem currently of limited clinical utility for identifying individuals at high self-harm risk.